Standard setting and internal validation of a novel approach adopted for assessing speaking - Zoltán Lukácsi (Peoples' Friendship University of Russia (RUDN University), 2020)
In 2016, Euroexam International launched a complex and ambitious project to redesign the rating process and practice of its subjectively scored papers. As part of the project, a series of level-specific performance checklists were developed for speaking and writing. This paper reports on the standard setting and internal validation procedures for B2 speaking in English as a foreign language (EFL) as executed in Spring, 2020. The participants of the study were 8 EFL teachers and oral examiners from international backgrounds with varying degrees of expertise in language testing. The method adopted for standard setting was the Body of Work method. The participants were allocated into either of two groups working independently on a random sample of 32 audio-recorded live speaking paper performances in a counterbalanced design. The study found that (a) a level-specific 30-item checklist for EFL speaking at B2 can adequately replace the operational rating scales for pass/fail decisions; (b) the granular nature of the checklist renders it more capable of covering the targeted content areas; and (c) the explicit checklist statements support fairness, transparency and accountability.